Pengaruh Serbuk Daun Salam (Syzygium polyanthum) Terhadap Mortalitas Hama Kutu Beras (Sitophilus oryzae L.) - Nurfitriyani, Nurul; Gazali, Akhmad; Sari, Noorkomala (Universitas Lambung Mangkurat, 2025)
The rice commodity is an important food ingredient needed by consumers. These agricultural materials are stored in the warehouse. The pest that is a problem is the rice weevil. An alternative control method that can be carried outin an environmentally friendly manner is by using bay leaf powder pesticide. Bay leave scan be used as a natural pesticide because they contain chemical compounds in the form of flavonoids and essential oils. The essential oil contained in bay leaves is thought to repel insects. This research aims to determine the effect of giving bay leaf powder and the effective dose in controlling rice weevil pests. This research used a 1 factor Completely Randomized Design (CRD) experiment with 5 treatment levels, namely K0= 0 g, K1 = 5 g, K2 = 15 g, K3= 25 g, andK4 = 35 g. The results of the research showed that giving bay leaf powder did not have a significant effect on mortality, development of rice weevil pest populations, and reduction in rice weight. The highest percentage of mortality for Sitophilus oryzae in the treatment given K4 bay leaf powder (35 g of bay leaf powder) was17.5% with an average population of 8.25 individuals and a percentager eduction in rice weight of 1.46%. The lowest data was in the treatment without giving bay leaf powder K0(without giving bay leaf powder) with a value of 10% with a population of 9 individuals and a percentage reduction in rice weight of 1.875%.